HTLV-1 Tax-1 interacts with SNX27 to regulate cellular localization of the HTLV-1 receptor molecule, GLUT1 - Al-Saleem, Jacob (PLoS One, 2019)
An estimated 10–20 million people worldwide are infected with human T cell leukemia virus type 1 (HTLV-1), with endemic areas of infection in Japan, Australia, the Caribbean, and Africa. HTLV-1 is the causative agent of adult T cell leukemia (ATL) and HTLV-1 associated myopathy/tropic spastic paraparesis (HAM/TSP). HTLV-1 expresses several regulatory and accessory genes that function at different stages of the virus life cycle. The regulatory gene Tax-1 is required for efficient virus replication, as it drives transcription of viral gene products, and has also been demonstrated to play a key role in the pathogenesis of the virus. Several studies have identified a PDZ binding motif (PBM) at the carboxyl terminus of Tax-1 and demonstrated the importance of this domain for HTLV-1 induced cellular transformation. Using a mass spectrometry-based proteomics approach we identified sorting nexin 27 (SNX27) as a novel interacting partner of Tax-1. Further, we demonstrated that their interaction is mediated by the Tax-1 PBM and SNX27 PDZ domains. SNX27 has been shown to promote the plasma membrane localization of glucose transport 1 (GLUT1), one of the receptor molecules of the HTLV-1 virus, and the receptor molecule required for HTLV-1 fusion and entry. We postulated that Tax-1 alters GLUT1 localization via its interaction with SNX27. We demonstrate that over expression of Tax-1 in cells causes a reduction of GLUT1 on the plasma membrane. Furthermore, we show that knockdown of SNX27 results in increased virion release and decreased HTLV-1 infectivity. Collectively, we demonstrate the first known mechanism by which HTLV-1 regulates a receptor molecule post-infection.